Efektifitas Edukasi “Biasakan Suntik Insulin (Bisul)” terhadap Kemandirian Pasien Diabetes Mellitus dalam Pemberian Insulin di RSU Islam Harapan Anda Kota Tegal - Farah El Yusri; Apriliani Yulianti; Sri Wahyuni (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes mellitus is a disease caused by inadequate insulin secretion or impaired insulin function. One treatment for DM is insulin administration. To make insulin administration easier and more effective, the